Participation in future planning by community‐dwelling older Australians receiving aged care services: Findings from a cross‐sectional survey. (14th March 2021) - Bryant, Jamie; Hobden, Breanne; Waller, Amy; Clapham, Matthew; Sanson‐Fisher, Robert
Abstract: Objectives: To determine in a sample of older community‐dwelling adults: (1) the proportion who have engaged in medical and financial planning; (2) the factors associated with advance care directive (ACD) completion and substitute decision maker (SDM) appointment; and (3) for those without an ACD, what might prompt completion. Methods: A cross‐sectional survey was undertaken with individuals receiving community aged care services in metropolitan and regional communities. Data collection was conducted by case managers during a home visit. Results: Overall, 158 individuals ( M = 78 years, SD = 8.7) participated (53.5% consent rate). Financial planning participation (will = 85%; enduring power of attorney = 66%) was higher than medical planning participation (SDM: 54%; ACD: 30%). No health status factors were significantly associated with ACD completion or SDM appointment. Diagnosis of a life‐limiting illness was most likely to prompt ACD completion (77.6%). Conclusions: One third of older people residing in the community have completed an ACD. Strategies to improve uptake in this vulnerable population require further exploration.